DEVELOPMENT OF DOWNSTREAM AGRIBUSINESS IN THE CONTEXT OF INCREASING VALUE ADDED PRODUCTS CPO - Diana Sulianti K. Tobing (UPT Penerbitan Universitas Jember, 2012)
Commodity palm oil has a very large role in the economy of Indonesia. The Government supports the growth of the business world for oil palm plantations pengembangkan either increase the intensification and extensification in the new land. This study aims to provide an overview of the development of agribusiness in Indonesia downstream palm oil and efforts are made to the downstream industry in order to increase value-added agribusinesses downstream palm oil in Indonesia. The method used is descriptive method by which data is obtained from the Ministry of Agriculture, GAPKI, Statistics Indonesia, Ministry of Industry and Apolin. At the end of the discussion suggested to accelerate downstream process in Indonesia where the key lies in the macroeconomic management of the infrastructure and interest rates, stabilization policy linkages in the domestic cooking oil prices for inflation, as well as a consistent national energy policy.